FLEXIBLE LABOR: A SCHEME FOR WOMEN’S INCLUSION OR EXCLUSION IN TURKEY? - Esra Koten (European Scientific Journal, ESJ, 2015)
As the notion of flexible working hours, which frequently is accepted as a criterion associated and identified with the post-industrialized societies, has penetrated and been adopted by the Turkish labor force as well, the issue of women working in densely urban areas being subjected to unsecured labor practices is gaining prevalence. The purpose of this article is to evaluate and document the perception of women who work in the service industry of the above-mentioned societies by their male counterparts who participate in the same sector. To that end, in-depth interviews were conducted with twenty white-collar male employees in Turkey. The findings hence obtained suggest that, especially in those businesses where flexible hours and working space is demanded, the women are looked down upon by their male counterparts. The interviewed men perceive and prioritize the primary space and responsibilities of women as those confined to the traditional boundaries of home and family. As a consequence, rather than being accepted as a legitimate player of the work force with flexible hours, women are frequently trapped into their traditional role of a homemaker and whereby are, in effect, even further excluded from the labor force.